A novel model of home-based, patient-tailored and mobile application-guided cardiac telerehabilitation in patients with atrial fibrillation: A randomised controlled trial. (January 2022) - Cai, Cheng; Bao, Zhipeng; Wu, Nan; Wu, Fengming; Sun, Guozhen; Yang, Gang; Chen, Minglong
Objective: To assess the effectiveness of tele-monitored cardiac rehabilitation in patients who have undergone ablation for atrial fibrillation. Design: Single-centre, prospective, assessment-blinded, randomised controlled trial. Setting: Domiciliary rehabilitation with support from a tertiary care hospital. Subjects: One hundred patients who underwent ablation for atrial fibrillation were recruited. Interventions: Participants were randomly allocated to a 12-week standard rehabilitation treatment (control group) or a comprehensive, domiciliary, mobile application-guided and tele-monitored cardiac rehabilitation program (intervention group) in a 1:1 fashion. Main outcome measures: The primary endpoint was the improvement in VO2peak . The secondary outcomes included adherence, physical activity, beliefs related to cardiovascular disease and exercise self-efficacy. Results: Ninety-seven patients completed follow-up. The mean VO2peak increased significantly in both the intervention group ( n  = 49) (baseline vs 12 weeks: 19.1 ± 4.7 vs 27.3 ± 5.6 ml/(min kg), P  < 0.01) and the control group ( n  = 48) (baseline vs 12 weeks: 18.7 ± 4.9 vs 22.9 ± 6.3 ml/(min kg), P  < 0.01). The results of the between-group analysis of aerobic capacity were significantly in favour of the intervention group. During the 12-week program, patients in the intervention group exhibited better adherence than those in the control group. Moreover, self-reported physical activity improved more in the intervention group than in the control group, as did the beliefs related to cardiovascular disease and exercise self-efficacy (all P  < 0.01). Conclusions: Our domiciliary, mobile application-guided and tele-monitored cardiac rehabilitation program could lead to a more significant improvements in physical fitness, adherence and health beliefs than standard cardiac rehabilitation in patients who have undergone ablation for atrial fibrillation.